PENGARUH JUMLAH ANGGOTA DAN JUMLAH SIMPANAN TERHADAP SHU PADA KOPERASI KREDIT SERVIAM KUPANG - Soares, Yohanes (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Decreased percentage of the number of members of the Serviam Kupang Credit Cooperative in 2020 - 2021. Decreased percentage of SHU acquisition of the Serviam Kupang Credit Cooperative in 2020 - 2021. The multiple linear regression technique was used to determine whether or not there was an influence of the variables number of members and amount of savings on the SHU variable at the Serviam Kupang Credit Cooperative. After testing it using the t-test, it is known that the number of members (X1) has no effect on the acquisition of SHU (Y), while the number of savings (X2) has an effect on SHU (Y). after being tested using the f-test simultaneously, the number of members (X1) and the amount of deposits (X2) have a significant effect on the acquisition of SHU (Y). The magnitude of the influence of the number of members (X1) and the amount of savings (X2) on the acquisition of SHU at the Serviam Credit Cooperative shows a coefficient of determination (r2) of 0.957%. This figure means that the number of members and the amount of savings influence the SHU by 0.957%, while the remainder (100%-0.957% 99.043%) is influenced by other variables not examined in this research, such as the amount of loans and income. It is hoped that the management and management of the Serviam Kupang Credit Cooperative can increase the amount of savings so that the Cooperative's SHU can increase.